Δ13C methane source signatures from tropical wetland and rice field emissions. (24th January 2022) - France, James L.; Fisher, Rebecca E.; Lowry, David; Allen, Grant; Andrade, Marcos F.; Bauguitte, Stéphane J.-B.; Bower, Keith; Broderick, Timothy J.; Daly, Michael C.; Forster, Grant; Gondwe, Mangaliso; Helfter, Carole; et al.
Abstract : The atmospheric methane (CH4 ) burden is rising sharply, but the causes are still not well understood. One factor of uncertainty is the importance of tropical CH4 emissions into the global mix. Isotopic signatures of major sources remain poorly constrained, despite their usefulness in constraining the global methane budget. Here, a collection of new δ 13 CCH4 signatures is presented for a range of tropical wetlands and rice fields determined from air samples collected during campaigns from 2016 to 2020. Long-term monitoring of δ 13 CCH4 in ambient air has been conducted at the Chacaltaya observatory, Bolivia and Southern Botswana. Both long-term records are dominated by biogenic CH4 sources, with isotopic signatures expected from wetland sources. From the longer-term Bolivian record, a seasonal isotopic shift is observed corresponding to wetland extent suggesting that there is input of relatively isotopically light CH4 to the atmosphere during periods of reduced wetland extent. This new data expands the geographical extent and range of measurements of tropical wetland and rice δ 13 CCH4 sources and hints at significant seasonal variation in tropical wetland δ 13 CCH4 signatures which may be important to capture in future global and regional models. This article is part of a discussion meeting issue 'Rising methane: is warming feeding warming? (part 2)'.